Pengaruh Komunikasi dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Koperasi Tuwuh Sari Kecamatan Angsana Kabupaten Tanah Bumbu - Muhammad Jahri; Sugiyanto; Dodik Jatmika; Nurhikmah; Diana (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
All organizations strive to achieve their goals to the fullest. Organizational goals can be achieved with good employee performance. Employee performance is influenced by communication and motivation. To analyze the effect of communication and motivation on employee performance at the Tuwuh Sari Cooperative, Angsana District, Tanah Bumbu Regency, it is necessary to do. The research method uses quantitative methods. The population of this research is the employees of the Tuwuh Sari Cooperative. The sampling technique used is the census. The sample of this study amounted to 40 employees. data collection using questionnaires. Data analysis used multiple linear regression analysis. The results showed that communication and motivation affected the performance of the employees of the Tuwuh Sari Cooperative, Angsana District, Tanah Bumbu Regency. Motivation has a dominant effect on the performance of the employees of the Tuwuh Sari Cooperative. However, these two variables have a significant effect on employee performance. Thus, it is suggested that communication and motivation need to be improved because these two variables improve employee performance.